Incidence, causes, and outcomes of renal failure among cirrhotic patients - Morsy, Khairy H; Mekky, Mohamed A.; Abdel-Malek, Mohamed O.; Abbas, Wael A. (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To evaluate the incidence, risk factors of RF among cirrhotic and its impact on patient’s outcome. Materials and Methods: A total of 573 cirrhotic patients were evaluated for renal failure (RF) and its causes, 212 patients (37%) were enrolled. Results: Majority of the patients had post hepatitis C liver disease (n=190, 89.6%) with Child-Pugh score C (88.2%), HCC was in 21.2% of cases baseline characteristics. Infections were observed in 45.8% (n=97) of patients whereas, spontaneous bacterial peritonitis (SBP) was the most type of infection (19.3%) among cirrhotic patients with renal failure, followed by pneumonia (9.9%). Infection-induced represents 30.2% followed by hypovolemia (29.7%), whereas HRS was in 11.3%. Reversibility of the condition was seen in 81 patients (38.2%), whereas mortality was seen in 58 (27.4%) patients of RF. The reversibility was more common in the patients with infection, followed by hypovolemia. Mortality was higher in the patients with HRS followed by parenchymal renal disease. Conclusion: Infection-induced and hypovolemic-induced RF represent the most common and also the most correctable causes and must be considered in management protocols for early detection and treatment that will serve for a better prognosis.